A Comprehensive Review of the Effects of Hyoscine Butylbromide in Childhood - Vázquez Frias, Rodrigo; Hörning, André; Boggio Marzet, Christian; Michel, Martin C. (Journal of Clinical Medicine, 2025)
Background/Objectives: Hyoscine butylbromide (HBB) is a spasmolytic drug classified as indispensable by the World Health Organization. While mostly used in adults, it is also approved for use in adolescents and children aged 6 years and older. We have comprehensively reviewed the efficacy and safety of HBB in approved and off-label childhood indications. Results: Childhood studies covered an age range starting as early as 2 days. A randomized controlled trial (RCT) found a similar efficacy compared to paracetamol in the approved indication of abdominal cramps and pain. Among off-label uses, several studies demonstrate efficacy in general anesthesia and various diagnostic procedures, but the largest body of evidence relates to use in childbirth/labor, including 17 RCTs. While these largely focused on efficacy outcomes on the mother, fetal safety outcomes were reported in 12 of these studies, mostly as effects on the APGAR score and/or heart rate. The overall evidence supports safety in infants and children including those younger than the approved use age of 6 years and older. Conclusions: While only limited pediatric efficacy data from RCTs are available in the approved indications, data from thousands of patients in RCTs, case series, and non-randomized trials do not raise concerns on the safety and tolerability of HBB in childhood. Additional dedicated childhood studies, particularly RCTs, on efficacy are recommended.
CRIS-Team Scopus Importer:2025-05-23
Keywords: abdominal cramps; abdominal pain; childbirth; children; hyoscine butylbromide; infants; vomiting

Adenosine-generating CD39+ plasmablasts predispose to successful infliximab therapy in pediatric IBD - Schnell, Alexander; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Schuh, Wolfgang; Regensburger, Adrian; Rauh, Manfred; Wölfle, Joachim; Hörning, André (Life Science Alliance, 2025)
B cells display several immunoregulatory mechanisms including the production of interleukin-10. Ectonucleotidases like CD39 and CD73 influence immune homeostasis by metabolizing eATP and generating immunosuppressive adenosine. The major objective was to examine the expression of those immunoregulatory molecules on B-cell subsets, and, more specifically, to determine their association with an infliximab (IFX) treatment in a pediatric inflammatory bowel disease (IBD) cohort. 42 IBD patients were assessed for IFX response after 12 mo of therapy and compared against 14 healthy controls (HC). Although IL10-producing plas-mablasts were decreased in IFX nonresponders (NRS), we de-tected an up-regulation of CD39 on plasmablasts and increased fractions of CD39/CD73-co-expressing naïve and memory B cells in responding patients (RS). In addition, B cells of responders proved to have superior ATP degradation capacities and aden-osine production before therapy initiation compared with NRS and HC. Moreover, IFX nonresponders had a marked deficiency of α4β7hi plasmablasts, whereas both cohorts had fewer CCR9-expressing plasmablasts. Consequently, CD39+ plasmablasts were decreased in biopsies of inflamed mucosal tissues, espe-cially in IFX nonresponders. Our results highlight the regulatory potential of CD39/CD73-expressing B cells in pediatric IBD and suggest CD39+ plasmablasts as a potential determinant of a successful immunosuppressive therapy with IFX.
CRIS-Team Scopus Importer:2025-05-02

A Half-Century of Heterotopic Heart Transplantation in Mice: The Spearhead of Immunology Research - Yin, Decheng; Dewald, Oliver; Peng, Xiangyu; Nie, Wenlong; Rong, Song; Dudziak, Diana; Lehmann, Christian; Hörning, André; Fu, Jian (Transplantology, 2024)
Since the success of solid organ transplants, such as human kidneys, livers and hearts, from the 50s to the 60s in the last century, the field of organ transplantation has progressed rapidly. Mainly due to modifications in surgical operation techniques and improvements in immunosuppressive therapy regimes, organ survival time can now be greatly prolonged. This progress has also been dependent upon the availability of appropriate animal models for organ transplantation. Therefore, the mouse heart transplantation model has developed into an irreplaceable research model for solid organ transplantation, providing indelible contributions to the field. In this review, we will provide an overview of the technical developments in murine heart transplantation, as well as its historical and current role for alloimmune research. Further, we will describe its current fields of application and its scientific achievements before we discuss potential future applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heterotopic heart transplantation; immunology; murine transplantation

A Modified Surgical Technique for Kidney Transplantation in Mice - Yin, Decheng; Fu, Jian; Chen, Rongjun; Shushakova, Nelli; Allabauer, Ida; Wei, Xinyi; Schiffer, Mario; Dudziak, Diana; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2022)
Kidney transplantation in mice is a complicated and challenging surgery procedure. There are very few publications demonstrating the key steps of this operation. Therefore, this article introduces the technique and points out the surgical caveats associated with this operation. In addition, important modifications in comparison to the conventional procedure are demonstrated. Firstly, a patch of the abdominal aorta is cut and prepared so that the proximal bifurcations of the renal artery, including the ureteral artery are transected together with the donor kidney en bloc. This reduces the risk of a ureter necrosis and avoids the development of a urinary tract occlusion. Secondly, a new method of the vascular anastomosis is demonstrated that allows the operator to flexibly increase or decrease the size of the anastomosis after renal transplant reperfusion has already been initiated. This avoids the development of vessel strictures and intraabdominal bleeding. Thirdly, a technique that enables the anastomosis of the delicate donor ureter and the recipient bladder that does not cause a trauma is shown. Adopting this protocol can shorten the operation time and reduces the damage to the recipient's bladder, thereby significantly increasing the operation success rate for the recipient mice.
CRIS-Team Scopus Importer:2022-08-19

Analysis of CFTR mRNA and Protein in Peripheral Blood Mononuclear Cells via Quantitative Real-Time PCR and Western Blot - Schnell, Alexander; Tamm, Stephanie; Hedtfeld, Silke; Rodriguez Gonzalez, Claudio; Hörning, André; Lachmann, Nico; Stanke, Frauke; Dittrich, Anna Maria; Munder, Antje (International Journal of Molecular Sciences, 2024)
The Cystic Fibrosis Conductance Transmembrane Regulator gene encodes for the CFTR ion channel, which is responsible for the transport of chloride and bicarbonate across the plasma membrane. Mutations in the gene result in impaired ion transport, subsequently leading to perturbed secretion in all exocrine glands and, therefore, the multi-organ disease cystic fibrosis (CF). In recent years, several studies have reported on CFTR expression in immune cells as demonstrated by immunofluorescence, flow cytometry, and immunoblotting. However, these data are mainly restricted to single-cell populations and show significant variation depending on the methodology used. Here, we investigated CFTR transcription and protein expression using standardized protocols in a comprehensive panel of immune cells. Methods: We applied a high-resolution Western blot protocol using a combination of highly specific monoclonal CFTR antibodies that have been optimized for the detection of CFTR in epithelial cells and healthy primary immune cell subpopulations sorted by flow cytometry and used immortalized cell lines as controls. The specificity of CFTR protein detection was controlled by peptide competition and enzymatic Peptide-N-Glycosidase-F (PNGase) digest. CFTR transcripts were analyzed using quantitative real-time PCR and normalized to the level of epithelial T84 cells as a reference. Results: CFTR mRNA expression could be shown for primary CD4+ T cells, NK cells, as well as differentiated THP-1 and Jurkat T cells. In contrast, we failed to detect CFTR transcripts for CD14+ monocytes and undifferentiated THP-1 cells, as well as for B cells and CD8+ T cells. Prominent immunoreactive bands were detectable by immunoblotting with the combination of four CFTR antibodies targeting different epitopes of the CFTR protein. However, in biosamples of non-epithelial origin, these CFTR-like protein bands could be unmasked as false positives through peptide competition or PNGase digest, meaning that the observed mRNA transcripts were not necessarily translated into CFTR proteins, which could be detected via immunoblotting. Our results confirm that mRNA expression in immune cells is many times lower than in that cells of epithelial origin. The immunoreactive signals in immune cells turned out to be false positives, and may be provoked by the presence of a high-affinity protein with a similar epitope. Non-specific binding (e.g., Fab-interaction with glycosyl branches) might also contribute to false positive signals. Our findings highlight the necessity of accurate controls, such as CFTR-negative cells, as well as peptide competition and glycolytic digest in order to identify genuine CFTR protein by immunoblotting. Our data suggest, furthermore, that CFTR protein expression data from techniques such as histology, for which the absence of a molecular weight or other independent control prevents the unmasking of false positive immunoreactive signals, must be interpreted carefully as well.
CRIS-Team Scopus Importer:2024-07-12
Keywords: CFTR; cystic fibrosis; expression; immune cell lines; immune cells; leukocytes; protein; qPCR; RNA; Western blot

Association of clinical factors with postoperative complications of esophageal atresia - Besendörfer, Manuel; Müller, Hanna; Weiss, Christel; Wagner, Alexandra; Schellerer, Vera; Hörning, André; Diez, Sonja (Pediatrics and Neonatology, 2020)
Background: Esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) remains one of the most common gastrointestinal neonatal malformations. Even though postoperative management is standardized, it differs between hospitals and disease-associated clinical factors that may play a role in outcome have not yet been assessed in detail. Methods: In this monocentric retrospective study, data of 43 patients with EA between 2010 and 2018 were analyzed. Analysis includes assessment of the clinical background, surgical technique, postoperative management including application of continuous muscle relaxation (CMR), influence of coagulation parameters such as factor XIII and incidence of complications. Results: 21 patients (49%) were preterm infants with birth weights between 490 and 2840 g (median 1893 g). Only 35% (n = 15) presented without any concomitant malformations. Within the entire study population, representing Vogt II, IIIb and IIIc, we observed an association between the development of a postoperative pneumothorax and anastomotic failure (AF) (p = 0.0013). Furthermore, pneumothorax was associated with anastomotic stenosis (AS) in Vogt IIIb patients (p = 0.0129). CMR (applied since March 2017 in 7 patients in an attempt to prevent anastomotic problems due to high complication rates) and coagulation factor XIII did not significantly correlate with postoperative outcome. Conclusion: Appearance of pneumothorax was correlated with postoperative complications. These children should be monitored carefully in closer scheduled gastroenterological follow-up esophago-gastro-duodenoscopies. CMR and factor XIII substitution did not reduce anastomotic leakage but should be tested within an enlarged study population.
CRIS-Team Scopus Importer:2020-10-23
Keywords: continuous muscle relaxation; esophageal surgery; neonatal surgery; pneumothorax; postoperative relaxation

Blood circuit reconstruction in an abdominal mouse heart transplantation model - Yin, Decheng; Fu, Jian; Allabauer, Ida; Witzke, Oliver; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2021)
The surgical technique of heterotopic abdominal heart transplantation in mice is a standard model for research in transplantation immunology. Here, the established technique for a modified blood circuit reconstruction in a heterotopic abdominal heart transplantation model is presented. This method uses the intrathoracic inferior vena cava (IIVC) instead of the pulmonary artery of the donor heart for the anastomosis to the inferior vena cava of the recipient. It is facilitating and improving success rates for abdominal heart transplantation in mice.
CRIS-Team Scopus Importer:2021-07-02

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Contrast-Enhanced Multispectral Optoacoustic Tomography for Functional Assessment of the Gastrointestinal Tract - Paulus, Lars-Philip; Bühler, Adrian; Wagner, Alexandra; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Rother, Ulrich; Eckstein, Markus; Lang, Werner; Hörning, André; et al. (Advanced Science, 2023)
Real-time imaging and functional assessment of the intestinal tract and its transit pose a significant challenge to conventional clinical diagnostic methods. Multispectral optoacoustic tomography (MSOT), a molecular-sensitive imaging technology, offers the potential to visualize endogenous and exogenous chromophores in deep tissue. Herein, a novel approach using the orally administered clinical-approved fluorescent dye indocyanine green (ICG) for bedside, non-ionizing evaluation of gastrointestinal passage is presented. The authors are able to show the detectability and stability of ICG in phantom experiments. Furthermore, ten healthy subjects underwent MSOT imaging at multiple time points over eight hours after ingestion of a standardized meal with and without ICG. ICG signals can be visualized and quantified in different intestinal segments, while its excretion is confirmed by fluorescent imaging of stool samples. These findings indicate that contrast-enhanced MSOT (CE-MSOT) provides a translatable real-time imaging approach for functional assessment of the gastrointestinal tract.
CRIS-Team Scopus Importer:2023-06-30
Keywords: indocyanine green; intestine; multispectral optoacoustic tomography; optoacoustics; photoacoustics

Current Role of Monoclonal Antibody Therapy in Pediatric IBD: A Special Focus on Therapeutic Drug Monitoring and Treat-to-Target Strategies - Claßen, Merle; Hörning, André (Children, 2023)
In the last two decades, biologicals have become essential in treating children and adolescents with inflammatory bowel disease. TNF-α inhibitors (infliximab, adalimumab and golimumab) are preferentially used. Recent studies suggest that early application of TNF-α inhibitors is beneficial to inducing disease remission and preventing complications such as development of penetrating ulcers and fistulas. However, treatment failure occurs in about one third of pediatric patients. Particularly, children and adolescents differ in drug clearance, emphasizing the importance of pharmacokinetic drug monitoring in the pediatric setting. Here, current data on the choice and effectiveness of biologicals and therapeutic drug monitoring strategies are reviewed.
CRIS-Team Scopus Importer:2023-05-05
Keywords: biologics; Crohn’s disease; treatment optimization; trough levels; ulcerative colitis

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

Distribution and Cytokine Profile of Peripheral B Cell Subsets Is Perturbed in Pediatric IBD and Partially Restored during a Successful IFX Therapy - Schnell, Alexander; Schwarz, Benedikt; Wahlbuhl, Mandy; Allabauer, Ida; Hess, Merlin; Weber, Simone; Werner, Felix; Schmidt, Hannah; Rechenauer, Tobias; Siebenlist, Gregor; Kaspar, Sonja; Ehrsam, Christoph; et al. (Inflammatory Bowel Diseases, 2021)
Background: The role of B cells in inflammatory bowel disease (IBD) is ambiguous, as B cells may have both pathogenic and protective functions in IBD. We studied B cell subsets before and after initiation of an anti-tumor necrosis factor alpha (anti-TNFα) therapy in pediatric IBD. The aim of the study was to examine the behavior of B cells in pediatric IBD patients undergoing an anti-TNFα therapy and, more specifically, to clarify their association with a successful or an unsuccessful infliximab (IFX) treatment. Methods: A total of N = 42 pediatric IBD patients (Crohn disease, n = 30; ulcerative colitis, n = 12) for whom an anti-TNFα therapy with and without a concomitant azathioprine (AZA) medication was administered were recruited. Fourteen healthy age-matched children served as control patients. Blood samples were collected before initiation of the anti-TNFα therapy, before the fourth infusion at the end of the induction phase, and after 6 and 12 months under therapy maintenance. Flow cytometry (CD20, CD27, CD38, CD138) and intracellular staining (interleukin 10 [IL10], TNFα, granzyme B) were performed. Responders to successful IFX therapy were classified exhibiting a fecal calprotectin level of below 100 μg/g or achieving levels of <10% of the baseline value at initiation than at the end of the 12-month follow-up period. Results: Before initiation of anti-TNFα therapy, flow cytometry revealed increased percentages of naïve B cells whereas transitional B cells were reduced compared with those in the healthy control patients. The IL10-producing B cells of both ulcerative colitis and Crohn disease patients were reduced at the initiation of IFX therapy, whereas TNFα-producing transitional CD24hiCD38hi B cells in ulcerative colitis patients were increased compared with those in healthy control patients. After 12 months of therapy, we detected a significant increase of IL10-producing transitional B cells in responding patients. The IFX trough levels in the responding patients showed a significant increase until 6 months after IFX initiation, attaining mean values of 9.9 μg/mL, whereas the IFX dosage was significantly lower than that in the nonresponding patients. The IFX trough levels in AZA-treated patients reached earlier therapeutic levels than in patients without AZA comedication, whereas during the course of the IFX therapy, comedication with AZA had no significant effect on the outcome. Conclusions: Attaining a normalization of IL10 production among CD24hiCD38hi B cells after 12 months of therapy may represent additional information about the reconstitution of a patient's immune system in responding patients. The achievement of an IFX trough level of 10 μg/mL at 6 months of treatment is associated with a successful anti-TNFα therapy. In addition, AZA comedication supports an earlier achievement of therapeutic IFX trough levels.
CRIS-Team Scopus Importer:2021-02-26
Keywords: children; Crohn disease; TNFα inhibitor; transitional B cells; ulcerative colitis

Elexacaftor – Tezacaftor – Ivacaftor treatment improves systemic infection parameters and Pseudomonas aeruginosa colonization rate in patients with cystic fibrosis a monocentric observational study - Schnell, Alexander; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Wölfle, Joachim; Hörning, André (Heliyon, 2023)
Background & aims: The CFTR-modulating therapy Elexaftor – Tezacaftor - Ivacaftor (ETI) has been widely prescribed since its approval in 2020 in the European Union. The aim of this study was to methodically evaluate the effects of an ETI treatment on clinical, biochemical data and Pseudomonas colonization in order to demonstrate its efficacy. Methods: This prospective monocentric study comprised 69 patients diagnosed with cystic fibrosis aged at least 12 years and treated with ETI between September 2020 and November 2021. Clinical and laboratory data of each patient and study visit were collected before and after 24 weeks of ETI treatment. Follow-up status of Pseudomonas aeruginosa (PsA) colonization was assessed after one year of therapy by regularly determined sputum or throat swab samples. Results: Marked improvements biochemical markers of systemic inflammation as white blood cell count, levels of immunoglobulins A, G and M and albumin within 24 weeks of therapy were observed. ETI treatment proved to be effective as seen by amelioration of lung function and sweat chloride concentration. Assessment of PsA colonization status revealed a conversion from a positive to negative detection in 36% of the cases after one year of therapy. Conclusions: ETI treatment effectively improves systemic inflammation parameters and shows promising results in PsA status conversion.
CRIS-Team Scopus Importer:2023-06-02
Keywords: CFTR modulator; Clinical data; Cystic fibrosis; Elexacaftor; ETI; Inflammation markers; Ivacaftor; Kaftrio; Tezacaftor

Enteral Nutrition Therapies in Children with Crohn's Disease - Current Strategies and Possible Modes of Action Enterale Ernährungstherapien beim pädiatrischen M. Crohn Anwendungen und Wirkweise - Hörning, André; Schmidt-Choudhury, Anjona (Aktuelle Ernährungsmedizin, 2023)
Nutrition has an essential effect on the occurence and course of disease in inflammatory bowel disease. Several factors as for example breast feeding, fiber intake from fruit as well as the so called mediterranian diet have been identified as being protective with regard to developing IBD. On the other hand, intake of high levels of sugar, raw meat or ultraprocessed food is associated with a higher risk for a manifestation of IBD in genetically predisposed children. Nevertheless, the underlying mechanisms how exclusion diets alone or in combination with medication modulate intestinal microbiota lead to mucosal healing still have to be elucidated. Since there already exists knowledge on the influence of nutrition on treating or preventing IBD this should be implicated in therapeutic and prevention strategies.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CDED; EET; IBD; microbiota; nutrition

Eosinophilic esophagitis—an underestimated food allergy? Eosinophile Ösophagitis – Eine unterschätzte Nahrungsmittelallergie? - Hörning, André; Madisch, A. (Die Dermatologie, 2025)
Eosinophilic oesophagitis (EoE) is a chronic T2-inflammatory disease and can be figuratively referred to as atopic dermatitis of the oesophagus. It is an immune-mediated disease caused by food allergens and is histologically defined by eosinophilic infiltration and clinically characterised by symptoms of oesophageal dysfunction. In addition to reducing the currently still considerable diagnostic latency, the focus is on prioritising existing and new treatment options with the aim of ensuring effective patient care with improved quality of life in the long term.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Elimination diet; Eosinophilic infiltration; Esophageal dysfunction; Food allergens; Quality of life

Erratum: Zahn et al. Manipulation of medicinal products for oral administration to paediatric patients at a german university hospital: An observational study. Pharmaceutics 2020, 12, 583 - Zahn, Julia; Hörning, André; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmaceutics, 2021)
The authors wish to make the following corrections to the affiliation and acknowledgments part [1]. The affiliation of all of the authors of “Department of Paediatrics and Adolescent Medicine, Universitätsklinikum Erlangen, 91054 Erlangen, Germany”, should be “Department of Paediatrics and Adolescent Medicine, Universitätsklinikum Erlangen, Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), 91054 Erlangen, Germany”. The updated “Acknowledgments” section is as follows “The authors would like to thank the nursing staff for a valuable exchange on the subject of manipulation and the opportunity to observe dispensing of medicines in clinical practice. The present work was performed in (partial) fulfilment of the requirements for obtaining the degree Dr. rer. biol. hum.”. The authors would like to apologize for any inconvenience caused to the readers by these changes.
CRIS-Team Scopus Importer:2021-08-06

Exhausted Lag-3+ CD4+ T cells are increased in pediatric Inflammatory Bowel Disease. - Schnell, Alexander; Aicher, Carmen; Schnegelsberg, Philipp; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Rueckel, Aline; Regensburger, Adrian; Wölfle, Joachim; Hörning, André (Clinical and Experimental Immunology, 2025)
T cells are one of the main drivers of inflammatory bowel diseases (IBD). Infliximab (IFX) is used in the treatment of IBD as an anti-inflammatory drug to induce remission by neutralizing TNFα. We determined the individual chemokine/homing receptor and cytokine profile in pediatric IBD patients before and during IFX therapy to identify predictive biomarkers for therapy success. Peripheral blood CD4+ cells from pediatric patients with IBD were immunomagnetically isolated and either directly analyzed by FACS for cell distribution and chemokine/homing receptor expression or evaluated for cytokine production after in-vitro-stimulation. Twenty-one responders (RS) and 21 non-responders (NRS) were recruited. Before IFX therapy, flow cytometry revealed decreased percentages of naïve conventional T cells in pediatric IBD patients. The proportions of CD62-L+ T cells were decreased in both CD and UC therapy responders. The cytokine profile of T cells was highly altered in IBD patients compared to healthy controls (HC). During IFX therapy, the frequencies of conventional memory and regulatory memory T cells expanded in both cohorts. IFX response was marked by a decrease of α4β7+ and IFNγ+ memory T cells in both CD and UC. In contrast, frequencies of Lag-3+ T cells proved to be significantly increased in NRS. These observations were irrespective of the underlying disease. T cells of pediatric IBD patients display an activated and rather Th1/Th17-shifted phenotype. The increased expression of the checkpoint molecule Lag-3 on T cells of NRS resembles a more exhausted phenotype than in RS and HC which appeared to be a relevant predictive marker for therapy failure.
EVALuna2:582625

Familial homozygot hypobetalipoproteinemia (HHBL): A rare differentialdiagnosis of chronic diarrhea with malabsorption and hepatopathy Familiäre homozygote Hypobetalipoproteinämie (HHBL) Eine seltene Differenzialdiagnose bei chronischer Diarrhö mit Malabsorption und Hepatopathie - Hörning, André; Rieger, Daniel (Pädiatrische Praxis, 2022)
Not only hypercholesterolemia but also reduced cholesterol levels can indicate diseases that must be diagnosed and treated early to prevent progression or secondary organ manifestation. In cases of unclear hepatopathy, especially accompanied by failure to thrive and diarrhea, triglycerides, total cholesterol, and HDL and LDL cholesterol should always be determined. Decreased total cholesterol, LDL cholesterol and triglyceride levels as well as the presence of acanthocytes are indicative of an a- or hypobetalipoproteinemia and should be followed by molecular genetic testing. Differential diagnoses include secondary hypocholesterolemias and, especially in the presence of normal triglycerid levels, chylomicron retention disease. Decisive for the long-term prognosis of these diseases, especially abetalipoproteinemia and the homozygous form of hypobetalipoproteinemia, is the early implementation a fat reduced diet including a substitution of fat-soluble vitamins and essential fatty acids as well as close-meshed multidisciplinary care.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Abetalipoproteinemia; Hypo-triglyceridemia; Hypobetalipoproteinemia; Hypocholesterinemia; lipid metabolism disorder

Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Jüngert, Jörg; Galiano, Matthias; Meier, Norbert; Wölfle, Joachim; Schiffer, Mario; Hörning, André (Frontiers in Pediatrics, 2023)
Objectives: The survival of pediatric patients with short bowel syndrome has improved in recent years. Enteric hyperoxaluria as a pathophysiological consequence has been hardly addressed so far. It can be associated with nephrolithiasis, nephrocalcinosis or even renal insufficiency. We assessed the prevalence of hyperoxaluria and its pathogenic consequences in a retrospective single centre study over the last 12 years. Methods: We conducted an internal database search for all pediatric patients suffering from short bowel syndrome treated from 2010 to 2022 in the department of pediatric gastroenterology as well as the pediatric nephrology and dialysis unit. Out of 56 patients identified, 26 patients were analysed for etiology of short bowel syndrome, renal excretion of oxalate (24/26), remaining short bowel and large intestinal length as well as further clinical parameters such as eGFR, nephrocalcinosis/urinary stone formation or stool frequency. Results: Hyperoxaluria was detected in 14/26 patients (54%). Nephrocalcinosis was present in four patients. Out of these four patients, hyperoxaluria could be proven (21% of all hyperoxaluric patients) in three cases, one hyperoxaluric patient had nephrolithiasis (7%). In one patient hyperoxaluria lead to end stage renal disease. We found that 80% of patients with volvulus developed enteric hyperoxaluria. None of the investigated factors had an effect on oxalate excretion. Conclusion: Enteric hyperoxaluria is a relevant pathophysiological finding in patients with short bowel syndrome occurring in about 50% of our cohort with multiple pathogenic complications. Regular screening for hyperoxaluria may be implemented in medical care for patients with short bowel syndrome. If necessary, prophylaxis, e.g., dietary advice or metaphylaxis should be initiated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: enteric hyperoxaluria; hyperoxaluria; intestinal failure; kidney stone; nephrolithiasis; pediatric; short bowel syndrome

Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis

Manipulation of medicinal products for oral administration to paediatric patients at a german university hospital: An observational study - Zahn, Julia; Hörning, André; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmaceutics, 2020)
Pharmacotherapy in children requires medicinal products in age-appropriate dosage forms and flexible dose strengths. Healthcare professionals often encounter a lack of licensed and commercially available formulations, which results in the need for manipulation. This study aimed to investigate the nature, frequency and preventability of the manipulation of medicinal products before oral drug administration to paediatric inpatients in Germany. A prospective, direct observational approach was used. Two thousand and three medication preparation processes (MPP) in 193 patients were included in the analysis. Medicines were manipulated in 37% of oral administrations, affecting 57% of the patients. The percentage of manipulations was highest in infants/toddlers (42%) and lowest in adolescents (31%). Antiepileptics were most frequently manipulated (27%), followed by vitamins (20%) and drugs for acid-related disorders (13%). Fifty-six per cent of all manipulations were off-label. In 71% of these, no alternative appropriate medicinal product was commercially available. These results demonstrate that the manipulation of medicinal products before oral administration is common in paediatric wards in Germany. About half of the manipulations were off-label, indicating that no suitable formulation was available. Evidence-based guidelines for manipulations are required, with the overall aim of improving the safety of paediatric drug therapy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Age-appropriate formulation; Drug manipulation; Hospital; Off-label use/manipulation; Oral drug administration; Paediatrics

Mucosal Mast Cell Distribution in the Gastrointestinal Tract of Children: A Preliminary Study for Establishing Reference Values - Ehrsam, Christoph; Rechenauer, Tobias; Allabauer, Ida; Siebenlist, Gregor; Kaspar, Sonja; Rieger, Daniel; Schmid, Margit; Ruckel, Aline; Wölfle, Joachim; Hartmann, Arndt; Rieker, Ralf; Raithel, Martin; et al. (Journal of Pediatric Gastroenterology and Nutrition, 2022)
Objectives: The physiological number and distribution of mast cells (MCs) in the pediatric gastrointestinal (GI) tract is not well defined and reference values of normality are missing. To define a physiological and disease defining cut-off, a systematic histological exploration of MC distribution from the esophagus to the rectum in healthy as well as in patients with gastrointestinal food allergies (GFA) was performed. Methods: Nine pediatric subjects that exhibited unremarkable histopathological evaluations or underwent endoscopy for surveillance reasons after a previous polypectomy of single colonic juvenile polyps served as reference cohort. In all of these subjects, a chronic inflammatory disease (eg, inflammatory bowel disease, celiac disease) or allergy was excluded. In addition, a group of 15 patients with gastrointestinal complaints suspected to be caused by a GFA were investigated. Immunohistochemistry was performed from all biopsies using CD117 (c-Kit) as a reliable marker to identify MCs in the lamina propria. Results: There were distinct differences of MC counts in all parts of the pediatric GI tract. The highest counts of MCs in both symptomatic patients and control cohort, were found in the duodenum, terminal ileum, cecum and ascending colon. The lowest counts were found in the esophagus. Significant disparities between GFA and healthy subjects were found in the gastric corpus (22.1 +/- 4.0/ high power field [HPF] vs 32.0 +/- 10.1/HPF; P = 0.034) and ascending colon (44.8 +/- 10.4/HPF vs 60.4 +/- 24.3/HPF; P = 0.047). Conclusions: Mucosal MC counts in the pediatric GI tract are higher than previously reported, with a considerable overlap between healthy and GFA patients. These results provide detailed information on distribution and numbers of MCs in pediatric allergic patients while allowing estimates of physiological values in childhood for the first time. With regard to diagnostic procedures in GFA further laboratory parameters have to be integrated.
CRIS-Team WoS Importer:2022-01-07

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

Novel p.G250A Mutation Associated with Chronic Pancreatitis Highlights Misfolding-Prone Region in Carboxypeptidase A1 (CPA1) - Sandor, Mate; Thiel, Franziska G.; Schmid, Margit; Demcsak, Alexandra; Granda, Nataly C. Morales; Nemeth, Balazs Csaba; Vajda, Sandor; Hörning, André; Sahin-Toth, Miklos (International Journal of Molecular Sciences, 2022)
Inborn mutations in the digestive protease carboxypeptidase A1 (CPA1) gene may be associated with hereditary and idiopathic chronic pancreatitis (CP). Pathogenic mutations, such as p.N256K, cause intracellular retention and reduced secretion of CPA1, accompanied by endoplasmic reticulum (ER) stress, suggesting that mutation-induced misfolding underlies the phenotype. Here, we report the novel p.G250A CPA1 mutation found in a young patient with CP. Functional properties of the p.G250A mutation were identical to those of the p.N256K mutation, confirming its pathogenic nature. We noted that both mutations are in a catalytically important loop of CPA1 that is stabilized by the Cys248-Cys271 disulfide bond. Mutation of either or both Cys residues to Ala resulted in misfolding, as judged by the loss of CPA1 secretion and intracellular retention. We re-analyzed seven previously reported CPA1 mutations that affect this loop and found that all exhibited reduced secretion and caused ER stress of varying degrees. The magnitude of ER stress was proportional to the secretion defect. Replacing the naturally occurring mutations with Ala (e.g., p.V251A for p.V251M) restored secretion, with the notable exception of p.N256A. We conclude that the disulfide-stabilized loop of CPA1 is prone to mutation-induced misfolding, in most cases due to the disruptive nature of the newly introduced side chain. We propose that disease-causing CPA1 mutations exhibit abolished or markedly reduced secretion with pronounced ER stress, whereas CPA1 mutations with milder misfolding phenotypes may be associated with lower disease risk or may not be pathogenic at all.
CRIS-Team WoS Importer:2023-01-20
Keywords: pancreatitis; misfolding; endoplasmic reticulum stress; carboxypeptidase; genetic risk

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Pediatric Buried Bumper Syndrome: Diagnostic Validity of Transabdominal Ultrasound and Artificial Intelligence - Aguilar, Caroline; Regensburger, Adrian; Knieling, Ferdinand; Wagner, Alexandra; Siebenlist, Gregor; Wölfle, Joachim; Koehler, Henrik; Hörning, André; Jüngert, Jörg M. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-04

Pediatric multi-drug-resistant tuberculosis in Germany – diagnostic and therapeutic challenges of an “orphan disease” - Schäfer, Hannah Lena; Barker, Michael; Follmann, Peter; Günther, Annette; Hörning, André; Kaiser-Labusch, Petra; Kerzel, Sebastian; Maier, Christoph; Roth, Samra; Schmidt, Christian; Schütz, Katharina; Stehling, Florian; et al. (European Journal of Pediatrics, 2023)
Delay in diagnosing multidrug-resistant tuberculosis (MDR-pTB) in children prolongs time to effective treatment. Data on risk factors for pediatric MDR from low-incidence countries are scarce. Retrospective nationwide case–control study to analyze MDR-pTB cases in Germany between 2010 and 2020 in comparison to a drug-susceptible (DS)-pTB group. We included 52 MDR cases (24 tuberculosis (TB), 28 TB infection (TBI); mean age 7.3 years) and 56 DS cases (31 TB, 26 TBI; mean age 7.9 years). Groups were similar for sex, household size, and migration background. Compared to the DS group, more children with MDR were born in the Commonwealth of Independent States (CIS) (22% MDR-pTB vs. 13% DS-pTB, n.s.) and had more MDR index cases (94% MDR-pTB, 5% DS-pTB, p < 0.001). The interval between first healthcare contact and initiation of effective therapy was significantly longer in MDR-pTB (47 days) than in DS-pTB (11 days, p < 0.001), correlating with disease progression. Treatment for MDR-pTB was successful in 74%, but 22% experienced long-term adverse effects (e.g., hepatopathy, hearing loss). Conclusions: Close contact to MDR cases or birth in MDR-TB-high-incidence countries are risk factors for MDR-pTB. Early identification of potential MDR index cases by contact investigation, and susceptibility testing in children from high-burden MDR-TB countries are essential for timely diagnosis and treatment, reducing the severity of disease and treatment side effects. Trial Registration: Deutsches Register Klinischer Studien (https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00023817), DRKS00023817, 2020–09-08. What is Known: •Management of children with MDR-TB remains challenging due to difficulties in diagnosing MDR-TB (lack of information on MDR index case, lack of microbiological confirmation in paucibacillary disease). •Choice of treatment regimen and monitoring of side effects. What is New: •Children with an MDR-TB index or born in a MDR-TB-high-incidence country are at higher risk of developing MDR-TB in a low incidence country. •The time lag to initiate treatment in MDR-TB is longer than in DS-TB and MDR-TB treatment involves a higher risk of adverse effects in longer treatment regimens especially with injectables.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Children; Germany; Multicenter; Multidrug resistance (MDR); Tuberculosis

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19

Premature birth associated with a favorable course in gestational alloimmune liver disease (GALD): A case report - Mulzer, Linda-Marie; Reutter, Heiko Martin; Jüngert, Jörg M.; Knisely, A. S.; Schmid, Margit; Hörning, André; Morhart, Patrick (Frontiers in Pediatrics, 2023)
Gestational alloimmune liver disease (GALD) is a rare neonatal disorder with high mortality and morbidity. The patients come to caregivers' attention aged a few hours or days. The disease manifests as acute liver failure with or without siderosis. The differential diagnosis of neonatal acute liver failure (NALF) is broad, including mainly immunologic, infectious, metabolic and toxic disorders. The most common cause, however, is GALD followed by herpes simplex virus (HSV) infection. The best suited pathophysiological paradigm of GALD is that of a maternofetal alloimmune disorder. State of the art treatment combines intravenously administered immunoglobulin (IVIG) with exchange transfusion (ET). We report an infant born at 35 + 2 weeks' gestation in whom GALD had a favorable course, of interest because premature birth in our patient may have exerted protective aspects and lessened morbidity in that intrauterine exposure to maternal complement-fixing antibodies was shortened. The diagnosis of GALD was challenging and difficult. We suggest a modified diagnostic algorithm combining clinical findings with histopathologic findings in liver and lip mucosa and, if available, on abdominal magnetic resonance imaging-study focusing on the liver, spleen, and pancreas. This diagnostic workup must be followed by ET and subsequent administration of IVIG without delay.
CRIS-Team WoS Importer:2023-04-14

Reactivations of Latent Viral Infections Are Associated with an Increased Thr389 p70S6k Phosphorylation in Peripheral Lymphocytes of Renal Transplant Recipients - Cherneha, Maxim; Korth, Johannes; Kaulfuss, Meike; Trilling, Mirko; Widera, Marek; Rohn, Hana; Dolff, Sebastian; Babel, Nina; Hörning, André; Kribben, Andreas; Witzke, Oliver (Viruses, 2021)
Reactivations of BK polyoma virus (BKPyV) and human cytomegalovirus (HCMV) frequently cause life- and graft-threatening complications after renal transplantation. Both viruses are dependent on the mTOR pathway for replication. In this study we investigated the association of viral replication with mTOR activity in peripheral lymphocytes of renal transplant recipients. A flow-cytometry based assay for the measurement of Thr389 p70S6k phosphorylation, a surrogate marker of the mTOR pathway was established. Forty-eight adult renal transplant recipients were recruited to measure p70S6k activity in their peripheral blood mononuclear cells. This data set in conjunction with information concerning previous replication of BKPyV and HCMV was examined for correlations. Episodes of BKPyV replication were significantly associated with increased p70S6k phosphorylation in CD4+ T lymphocytes (p = 0.0002) and CD19+ B lymphocytes (p = 0.0073). HCMV infection of patients with a high-risk HCMV constellation of donor and recipient (D+/R-) was associated with increased p70S6k phosphorylation in CD19+ B lymphocytes (p = 0.0325). These associations were found to be independent of the trough levels of the immunosuppressive drugs. Conclusion: P70S6k phosphorylation in peripheral lymphocytes is associated with BKPyV reactivations and to a lesser extent with HCMV infections in renal transplant recipients.
CRIS-Team Scopus Importer:2021-04-16
Keywords: BK polyoma virus; human cytomegalovirus; p70 ribosomal S6 kinase; PyVAN; renal transplantation

Repeated CXCR4 Blockade by Plerixafor Attenuates Transplant Vasculopathy in Murine Aortic Allografts - Theil, Frank; Kuckhahn, Annika; Hörning, André; Völkl, Simon; Knab, Katharina; Fritz, Niklas; Gräbner, Cindy; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (Journal of Immunology, 2024)
Plerixafor, a hematopoietic stem cell mobilization agent, increases the peripheral blood content of effector and regulatory T cells and may have beneficial effects on cardiac allograft vasculopathy. The aim of the current study was to evaluate its effects in a murine aortic allograft model using different application procedures. Allogeneic donor aorta grafts (n 5 8/group) from C57BL/6 mice(H2b) were abdominally transplanted into CBA mice (H2k). Plerixafor application was performed either continuously for 14 d using abdominally implanted osmotic pumps (1 mg/kg/d) or i.p. with a single dose (1 and 5 mg/kg) on day 0 or pulsed injections of 1 mg/kg on days 0, 7, 14, and 21. Cell distribution was monitored by FACS. Aortic grafts were evaluated for neointima development by Elastica-van-Gieson on day 30. Immunofluorescence and intragraft gene expression analysis were performed. On day 14, significantly fewer hematopoietic stem cells were found in the bone marrow of all plerixafor-treated mice. In the pulsed application group, significantly more hematopoietic stem cells were found in the peripheral blood on day 14 (0.045 ± 0.002%; p < 0.01 [pulsed]; versus 0.0068 ± 0.002% [control]) and also more regulatory T cells. PCR revealed lower inflammatory cytokines. The luminal occlusion was significantly reduced in the pulsed treated group (33.65 ± 8.84 versus 53.13 ± 12.41) going along with decreased neointimal CD4+ T cell and plasmacytoid dendritic cell infiltration, as well as less smooth muscle cell proliferation. The application of plerixafor attenuates chronic rejection in aortic allografts via immunomodulatory effects. Injection of repeated low-dose plerixafor is the most effective application form in the aortic transplant model.
CRIS-Team Scopus Importer:2024-11-22

Reversing the Inflammatory Process—25 Years of Tumor Necrosis Factor-α Inhibitors - Muth, Katharina N.; Rech, Jürgen; Losch, Florian O.; Hörning, André (Journal of Clinical Medicine, 2023)
Immune-mediated inflammatory diseases, such as rheumatoid arthritis, psoriatic arthritis, peripheral and/or axial spondyloarthritis, Crohn’s disease, and ulcerative colitis, are characterized by molecular and cellular changes in the immune system. Due to the systemic nature of these diseases, organs such as the liver or cardiovascular system are often affected by the inflammatory process. Tumor necrosis factor-α inhibitor therapy reduces the activation of pro-inflammatory signaling cascades, mitigates the chronic inflammatory process by restoring cellular balance, and alleviates clinical consequences, such as pain and tissue damage.
CRIS-Team Scopus Importer:2023-09-01
Keywords: cytokines; immune-mediated inflammatory diseases; inflammation; liver; rheumatoid arthritis; tumor necrosis factor alpha-inhibitors

Routine Surveillance of SARS-CoV-2 Serostatus in Pediatrics Allows Monitoring of Humoral Response - Wachter, Felix; Knieling, Ferdinand; Raming, Roman; Simon, David; Wölfle, Joachim; Hörning, André; Neubert, Antje; Rauh, Manfred; Regensburger, Adrian (Microorganisms, 2023)
The occurrence of SARS-CoV-2 infections during the pandemic was mainly based on PCR testing of symptomatic patients. However, with new variants, vaccinations, and the changing of the clinical disease severity, knowledge about general immunity is elusive. For public health systems, timely knowledge of these conditions is essential, but it is particularly scarce for the pediatric population. Therefore, in this study, we wanted to investigate the spike and nucleocapsid seroprevalence in pediatric patients using routine residual blood tests collected during the pandemic. This prospective observational study was conducted over seven one-month periods. Herein, the latest four time periods (November 2021, January 2022, March 2022, and May 2022) are depicted. Each patient of a tertiary-care center in Germany was anonymized after collection of clinical diagnosis (ICD-10) and then routinely tested for the respective spike and nucleocapsid SARS-CoV-2 antibody titer. A total of 3235 blood samples from four time periods were included. Spike seroprevalence rose from 37.6% to 51.9% to 70.5% to 85.1% and nucleocapsid seroprevalence from 11.6% to 17.0% to 36.7% to 58.1% in May 2022. In detail, significant changes in seroprevalence between age groups but not between sex or diagnosis groups were found. Quantitative measures revealed rising spike and constant nucleocapsid antibody levels over the pandemic with a half-life of 102 days for spike and 45 days for nucleocapsid antibodies. Routine laboratory assessment of SARS-CoV-2 in residual blood specimens of pediatric hospitals enables monitoring of the seroprevalence and may allow inferences about general immunity in this cohort.
EVALuna2:547467
Keywords: COVID-19; pediatrics; seroprevalence; SARS-CoV-2; Omicron; surveillance

Significant advantages for first line treatment with TNF-alpha inhibitors in pediatric patients with inflammatory bowel disease – Data from the multicenter CEDATA-GPGE registry study - Claßen, Merle; de Laffolie, Jan; Claßen, Martin; Schnell, Alexander; Sohrabi, Keywan; Hörning, André (Frontiers in Pediatrics, 2022)
Background and aims: In recent years, biological agents, such as anti-TNF-α blockers, have been introduced and have shown efficacy in pediatric patients with inflammatory bowel disease (IBD). Here, the prescription mode differentiated into a first/second line application, and efficacy and side effects are evaluated beginning from 2004 until today. Methods: Statistical analyses of the prospective and ongoing CEDATA multicenter registry data from the Society of Pediatric Gastroenterology and Nutrition (GPGE) were performed for patients receiving a biological agent at least once during the period from June 2004 until November 2020 (n = 487). The analyzed parameters were patient demographics, disease extent and behavior, prior or concurrent therapies, duration and outcome of biological therapy, disease-associated complications, drug-related complications, laboratory parameters and treatment response as determined by the Physician’s Global Assessment. Results: Crohn’s disease (CD) was present in 71.5% of patients, and 52% were boys. Patients showed high disease activity when receiving a first-line TNF-α blocker. After 2016, patients who failed to respond to anti-TNF-α induction therapy were treated with off-label biologics (vedolizumab 4.3% and ustekinumab 2.1%). Propensity score matching indicated that patients with CD and higher disease activity benefitted significantly more from early anti-TNF-α therapy. This assessment was based on a clinical evaluation and lab parameters related to inflammation compared to delayed second-line treatment. Additionally, first-line treatment resulted in less treatment failure and fewer extraintestinal manifestations during TNF-α blockade. Conclusion: First-line treatment with anti-TNF-α drugs is effective and safe. An earlier start significantly reduces the risk of treatment failure and is associated with fewer extraintestinal manifestations during longitudinal follow-up.
CRIS-Team Scopus Importer:2022-11-04
Keywords: anti-TNF-α inhibitor therapy; Crohn’s disease; first-line therapy; pediatric inflammatory bowel disease (IBD); ulcerative colitis

Stem Cell Mobilization by Plerixafor Has an Affirmatory Effect on the Development of Transplant Vasculopathy in a Murine Aortic Allograft Model - Theil, F.; Kuckhahn, A.; Hörning, André; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-05-20

TNF promotes DECTIN2 family C-type lectin receptor expression in human macrophages. - Haberkamp, Carl; Allabauer, Ida; Blaha, Niklas; Bodendorfer, Barbara; Cunningham, Sarah; Hörning, André; Lang, Roland (Journal of Leukocyte Biology, 2023)
TNF blockade constitutes an effective therapy for inflammatory bowel disease, yet increases the risk for infection, including active tuberculosis. The DECTIN2 family C-type lectin receptors MINCLE, MCL, and DECTIN2 sense mycobacterial ligands and activate myeloid cells. In mice, upregulation of DECTIN2 family C-type lectin receptor after stimulation with Mycobacterium bovis Bacille Calmette-Guérin requires TNF. Here, we investigated whether TNF controls inducible C-type lectin receptor expression in human myeloid cells. Monocyte-derived macrophages were stimulated with Bacille Calmette-Guérin and the TLR4 ligand lipopolysaccharide, and expression of C-type lectin receptor was analyzed. Bacille Calmette-Guérin and lipopolysaccharide strongly upregulated messenger RNA expression of DECTIN2 family C-type lectin receptor but not of DECTIN1. Bacille Calmette-Guérin and lipopolysaccharide also induced robust production of TNF. Recombinant TNF was sufficient to upregulate expression of DECTIN2 family C-type lectin receptor. Blocking TNF with the TNFR2-Fc fusion protein etanercept abrogated, as expected, the effect of recombinant TNF and impaired induction of DECTIN2 family C-type lectin receptor by Bacille Calmette-Guérin and lipopolysaccharide. Flow cytometry confirmed upregulation of MCL at the protein level by recombinant TNF and showed inhibition of Bacille Calmette-Guérin-induced MCL by etanercept. To investigate the impact of TNF on C-type lectin receptor expression in vivo, we analyzed peripheral blood mononuclear cells of patients with inflammatory bowel disease and observed downregulation of MINCLE and MCL expression after therapeutic TNF blockade. Together, TNF is sufficient to upregulate DECTIN2 family C-type lectin receptor in human myeloid cells and contributes to this process after encounter with Bacille Calmette-Guérin or lipopolysaccharide. Impaired C-type lectin receptor expression in patients receiving TNF blockade may dampen the sensing of microbes and defense against infection.
EVALuna2:531674
Keywords: MINCLE; MCL; DECTIN2; TNF blockade; mycobacteria; inflammatory bowel disease

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Ultrasound in Pediatric Inflammatory Bowel Disease—A Review of the State of the Art and Future Perspectives - Hörning, André; Jüngert, Jörg; Siebenlist, Gregor; Knieling, Ferdinand; Regensburger, Adrian (Children, 2024)
Inflammatory bowel disease (IBD) comprises a group of relapsing, chronic diseases of the gastrointestinal tract that, in addition to adults, can affect children and adolescents. To detect relapses of inflammation, these patients require close observation, frequent follow-up, and therapeutic adjustments. While reference standard diagnostics include anamnestic factors, laboratory and stool sample assessment, performing specific imaging in children and adolescents is much more challenging than in adults. Endoscopic and classic cross-sectional imaging modalities may be invasive and often require sedation for younger patients. For this reason, intestinal ultrasound (IUS) is becoming increasingly important for the non-invasive assessment of the intestine and its inflammatory affection. In this review, we would like to shed light on the current state of the art and provide an outlook on developments in this field that could potentially spare these patients more invasive follow-up procedures.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Crohn’s disease; optoacoustics; pediatric inflammatory bowel disease; ulcerative colitis; ultrasound